Awareness Against Gender-Based Violence Among Undergraduate Students in a College of Far Western - Acharya, Devaka Kumari; Dhakal, Seema (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Gender-based violence among youths has become a worldwide public health problem that could be physical, sexual, psychological, and economic. Globally about 1 in 3 (30%) of women have been subjected to either physical and/or sexual intimate partner violence or non-partner sexual violence in their lifetime. The study aimed to find out the awareness against gender-based violence among undergraduate students. A descriptive cross-sectional study was conducted in Raghunath Adarsha Multiple Campus, Kailali District, among 195 undergraduate students studying Bachelor of Humanities(85 students) and Management (110 students). Methods: Non-probability total enumerative sampling technique was used to recruit the sample. Datawas collected from November to December 2023 with a self-administered structured questionnaire. Data were checked for completeness, coded, and entered into Statistical Package for Social Science(SPSS version 25). Data were analyzed by using descriptive statistics frequency, percentage, mean, andstandard deviation, and inferential statistics Chi-square was used to measure the association between awareness against gender-based violence and socio-demographic variables. Results: The study findings showed that 39.5% of respondents had an adequate level of awareness, 37.4% had a moderately adequate level of awareness, and 23.1% had an inadequate level of awareness against gender-based violence. There was a statistically significant association between the level of awareness and fathers’ education p= 0.001 and fathers’ occupation p = <0.001. Conclusions: The study concludes that only two-fifths of students at the undergraduate level are adequately aware of gender-based violence. Nearly one-fourth of students still are inadequately aware of gender-based violence. College authorities and health professionals need to conduct awareness programs against gender-based violence at college and community levels thus they can protect themselves from violence against their sex.